PERFORMANCE MEASUREMENT AND RISK MITIGATION OF PINEAPPLE SUPPLY CHAIN IN CENTRAL KALIMANTAN PROVINCE - Odi Andanu; Erni Dwi Puji Setyowati; Rakha Satya Idsan (Department of Agroindustrial Technology, Bogor Agricultural University, 2025)
Pineapple farmers and agro-processing businesses in Kapuas and Pulang Pisau face several risk. One significant risk is the lack of clarity regarding existing supply chain structures and performance, resulting in operational inefficiencies. This study aimed to identify and measure the performance of the pineapple agroindustry supply chain, analyze potential risks within the supply chain, and evaluate risk mitigation actions in the pineapple agroindustry located in Kapuas Regency and Pulang Pisau Regency, Central Kalimantan. The method used to analyze supply chain performance was the SCOR-AHP (Supply Chain Operations Reference-Analytic Hierarchy Process) method, while risk analysis was conducted using the HOR (House of Risk) method. The results showed that the highest supply chain performance score was attributed to the distributor, with a total score of 72.89, categorized as